ANALISIS PERBEDAAN RASIO PROFITABILITAS PERBANKAN SEBELUM DAN SESUDAH ADANYA LAYANAN KEUANGAN BERBASIS TEKNOLOGI (FINTECH) - Trisna Dewi, Ni Putu Gita; Badjra, Ida Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.08.TAHUN.2023, 2023)
Considering the rapid development of Fintech, especially Rural Banks are finding themselves in a competitive position due to the convenience and comfort provided by Financial Technology. The aim of the research is to investigate if there is a relation between the emergence of financial technology and rural bank profitability in Bali's province. Return on Assets (ROA), Return on Equity (ROE), Net Interest Margin (NIM), and Operational Expenses to Operating Income were the profitability ratios evaluated in this study.  The study's sample was 27 BPR Bali Province, which was determined using purposive sampling method. The statistical analyses were performed using the Paired T-Test and the Wilcoxon Signed Rank Test The findings of this study reveal that the ratios of Return On Assets (ROA), Return On Equity (ROE), Net Interest Margin (NIM), and Operational Expenses on Operating Income (BOPO) of Rural Banks in Bali Province change significantly before and after the emergence of Financial Technology